Mental health awareness among students in higher education - Ghazali, Nur Maisarah; Mohd. Sharif, Nur Fatehah; Ismail, Junaida; Azizan, Intan Syahriza (Faculty of Administrative Science and Policy Studies, 2024)
Health is the main key to human well-being. A healthy person can certainly play an active role in the development of religion, nation, and country. The World Health Organization (WHO) which was established in 1948, defines health as a physical, mental, and social state that is healthy, vigorous, intelligent, and free from any disease. This definition asserts that health status is supported by physical, mental, and social factors that are healthy, functional, fit, and not threatened by any disease that can harm people. Health is one of the main focuses of the Malaysian government nowadays. Mental health is a crucial aspect of every phase of human life, just as important as physical health. Mental health is seen from both good and bad aspects. In life, every person may sometimes have a mental state that is very healthy, but at other times, it is the opposite. When experiencing mental health problems, a person needs the help of others to overcome the problems he is facing. Mental health can have an impact on a person's daily life or future, including children and youth. Treating and protecting the mental health of children and youth is a very important aspect that can help better individual development in the future.